PERLAWANAN SEBAGAI ALASAN PENUNDAAN EKSEKUSI DAN SIKAP PENGADILAN DALAM PROSES PENYELESAIAN PERKARA PERDATA DI PENGADILAN NEGERI YOGYAKARTA - , Titin Apriani, Dr. Sutanto, SH., M.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed at examining, understanding and explaining the background to the resistance as a reason for postponing execution and identifying and understanding the attitude of the Court in facing the resistance to the execution. This research is an empirical juridical research. It was conducted in two stages, namely library research and field research to obtain primary data. The method and equipment which was necessary to collecting data in library research was carried out by documentation method and documentation study. Meanwhile, the field research was conducted by using interview method, and interview orientation, then the data were analyzed using descriptive qualitative method. Results and discussion of research indicated that resistance was often used as a reason to suspend the execution of the resistance either conducted by one of the parties and the third party. Basically, the resistance conducted by either party or the third party is basically not or almost not different. It only lies in the position of plaintiff in opposition and respondent in opposition. In principle, resistance do not suspend the execution, except it is immediately clear that the resistance is appropriate and reasonable so that the execution can be suspended at least until the verdict passed by the District Court. The attitude of the Court in facing the resistance to the execution is that the judge must be fair and objective, and will decide the resistance on a case-bycase basis. If the plaintiff in opposition can prove the reason of resistance, he will be stated as a good plaintiff in opposition. Otherwise, he is a bad plaintiff in opposition.